Integration of TRPC6 and NADPH oxidase activation in lysophosphatidylcholine-induced TRPC5 externalization - Chaudhuri, Pinaki (2017)
Fil: Chaudhuri, Pinaki. Cleveland Clinic. Department of Biomedical Engineering; Estados Unidos